2006
DOI: 10.1093/humrep/dei486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogenic xenobiotics on human and mouse spermatozoa

Abstract: Human and mouse sperm responses to genistein are very similar, but human gametes appear to be even more sensitive. The mechanism of action may involve unregulated stimulation of cAMP production, leading to significant acrosome loss, undesirable because already acrosome-reacted cells are nonfertilizing. Xenobiotics were even more effective in combination. Since simultaneous exposure to low concentrations of multiple xenobiotics is likely to occur in animals and humans, further investigation is needed to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 53 publications
1
44
0
2
Order By: Relevance
“…Although 17a-ethynylestradiol only seems to act at higher concentrations (R2 ng/ml), the combination of all substances with potential or confirmed estrogenic activity can further misbalance the physiology of epididymal spermatozoa. Furthermore some artificial compounds with estrogenic activity have a significant effect on sperm physiology at lower doses compared with the strongest natural estrogen such as E 2 (Fraser et al 2006, Sebkova et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Although 17a-ethynylestradiol only seems to act at higher concentrations (R2 ng/ml), the combination of all substances with potential or confirmed estrogenic activity can further misbalance the physiology of epididymal spermatozoa. Furthermore some artificial compounds with estrogenic activity have a significant effect on sperm physiology at lower doses compared with the strongest natural estrogen such as E 2 (Fraser et al 2006, Sebkova et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…In our experimental conditions, we detected a slight reduction in the percentage of viable sperm with high lipid membrane disorder. The role of genistein in capacitation is not well defined; Fraser et al [49] reported that genistein at low concentrations (1, 10 and 100 nmol L -1 ) accelerated the capacitation and acrosome loss in human spermatozoa measured by CTC staining. On the other hand, several studies have shown the capacity of genistein taken at a higher concentration to inhibit the progesterone-induced acrosome reaction [50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…genistein, daidzein, glycitein), for 2 months (Mitchell et al, 2001). To add more confusion, an in vitro study showed that low concentrations of genistein (1, 10 and 100 nM) caused an accelerated capacitation and acrosome loss in human spermatozoa (Fraser et al, 2006).…”
Section: Soy Phytoestrogens and Male Reproductive Functionmentioning
confidence: 99%
“…Phytoestrogens appear to act in a similar manner. In vitro experiments have shown that low concentrations of genistein, nonylphenol and 8-pre-nylnaringenin were more effective when used in combinations, rather than alone, in causing adverse effects on the key processes of capacitation and acrosome reaction both in human and mouse spermatozoa (Fraser et al, 2006). Recently, it has been reported in rat studies that alterations in male reproductive functions were more pronounced when co-exposed to a low dose of genistein (1 mg/kg/day) and the fungicide vinclozolin (1 mg/kg/day) from conception to adulthood (Eustache et al, 2009).…”
Section: Soy Phytoestrogens and Male Reproductive Functionmentioning
confidence: 99%